Evidence for a second ankylosing spondylitis-associated RUNX3 regulatory polymorphism. Issue 1 (8th February 2018) - Vecellio, Matteo; Cortes, Adrian; Roberts, Amity R; Ellis, Jonathan; Cohen, Carla Jayne; Knight, Julian C; Brown, Matthew A; Bowness, Paul; Wordsworth, Bryan Paul
Abstract : Objectives: To explore the functions of RUNX3 single nucleotide polymorphisms (SNPs) associated with ankylosing spondylitis (AS). Methods: Individual SNP associations were evaluated in 4230 UK cases. Their effects on transcription factor (TF) binding, transcription regulation, chromatin modifications, gene expression and gene interactions were tested by database interrogation, luciferase reporter assays, electrophoretic mobility gel shifts, chromatin immunoprecipitation and real-time PCR. Results: We confirmed the independent association of AS with rs4265380, which was robust (P=4.7×10 −6 ) to conditioning on another nearby AS-associated RUNX3 SNP ( rs4648889 ). A RUNX3 haplotype incorporating both SNPs was strongly associated with AS (OR 6.2; 95% CI 3.1 to 13.2, P=1.4×10 −8 ). In a large UK cohort, rs4265380 is associated with leucocyte counts (including monocytes). RUNX3 expression is lower in AS peripheral blood mononuclear cells than healthy controls (P<0.002), independent of rs4265380 genotype. Enhancer function for this RUNX3 region was suggested by increased luciferase activity (approximately tenfold; P=0.005) for reporter constructs containing rs4265380 . In monocytes, there was differential allelic binding of nuclear protein extracts to a 50 bp DNA probe containing rs4265380 that was strongly augmented by lipopolysaccharide activation. TF binding also included the histone modifier p300. There was enrichment for histone modifications associated with active enhancer elements (H3K27Ac and H3K79Me2) that may be allele dependent. Hi-C database interrogation showed chromosome interactions of RUNX3 bait with the nearby RP4-799D16.1 lincRNA. Conclusions: The association of AS with this RUNX3 regulatory region involves at least two SNPs apparently operating in different cell types. Monocytes may be potential therapeutic targets in AS.